(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to: motivational perseverance among female students in the kindergarten department. The researcher used the descriptive, correlational approach to achieve the research objectives. The research sample consisted of (400) female students who were selected by a simple random method in proportion and proportion from the female students of the kindergarten department in the College of Basic Education at Al-Mustansiriya University. The researcher used the first tool, the Motivational Perseverance Scale, and the researcher decided to adopt the Motivational Perseverance Scale by (Al-Dada, 2021), translated and developed by Constantin and others (Constantin, etal, 2012). It consists of (40) items and consists of five areas: (setting long-term goals). term, striving to achieve long-term goals, planning current tasks, tracking current tasks, and remembering unachieved goals). The researcher verified the psychometric properties of the scale through apparent validity as she presented the items to (12) experts, and constructive validity. After applying the tool to the research sample and analyzing the data using the statistical package, the researcher reached the following results: Female students in the kindergarten department are distinguished by motivational perseverance.